Automotive aerodynamics - Katz, Joseph, 1947- (Automotive series (Wiley), 2016)
Automotive aerodynamics Joseph Katz, San Diego State University, USA The automobile is an icon of modern technology because it includes most aspects of modern engineering, and it offers an exciting approach to engineering education. Of course there are many existing books on introductory fluid/aero dynamics but the majority of these are too long, focussed on aerospace and don't adequately cover the basics. Therefore, there is room and a need for a concise, introductory textbook in this area. Automotive aerodynamics fulfils this need and is an introductory textbook intended as a first course in the complex field of aero/fluid mechanics for engineering students. It introduces basic concepts and fluid properties, and covers fluid dynamic equations. Examples of automotive aerodynamics are included and the principles of computational fluid dynamics are introduced. This text also includes topics such as aeroacoustics and heat transfer which are important to engineering students and are closely related to the main topic of aero/fluid mechanics. This textbook contains complex mathematics, which not only serve as the foundation for future studies but also provide a road map for the present text. As the chapters evolve, focus is placed on more applicable examples, which can be solved in class using elementary algebra. The approach taken is designed to make the mathematics more approachable and easier to understand. Key features: - Concise textbook which provides an introduction to fluid mechanics and aerodynamics, with automotive applications - Written by a leading author in the field who has experience working with motor sports teams in industry - Explains basic concepts and equations before progressing to cover more advanced topics - Covers internal and external flows for automotive applications - Covers emerging areas of aeroacoustics and heat transfer Automotive aerodynamics is a must-have textbook for undergraduate and graduate students in automotive and mechanical engineering, and is also a concise reference for engineers in industry.